SOCIO-POLITICAL PROCESSES IN THE CITY OF SAMARKAND IN THE FIRST HALF OF THE XIX CENTURY - Rabbimova, A (Мир исследований, 2021)
In this article, the first half of the XIX century in the city of Samarkand was given more extensive information about socio-political processes.